Rendszerváltás képekben. Magyarország 1988-1990 - Elbert, Márta (Hungary : Fekete Doboz, 2004)
Rich in archival footage, this film is a visual narrative of the regime change in Hungary.
Duration: 01:16:00
Keywords: Documentary films